(untitled) (American Journal of Technology and Applied Sciences, 2023)
In this article we will study the technologization of the educational process in the 3rd grades, providing them with quality training, some technologies that are used in the modern educational process. Opinions were expressed about the use of the most common technologies used in the educational process.